The relationship between the form of coping and the intensity of anxiety and somatic complaints among heart-by-pass surgery patients - Biveinytė, S.; Laurinaitis, E.; Uždavinys, G. (Psichologija, 1996)
114 patients, 105 males, and 9 females were investigated the day before heart-by-pass surgery using the Freiburg Questionnaire of Coping with Illness (FKV), the Giessen Questionnaire of Somatic Complaints (GBB), and the State-Trait Anxiety Inventory. The same patients were asked to answer the STAI and GBB on the 4th-6th day after their surgery. The results show a positive relationship between all forms of coping and physical exhaustion the day before the surgery. The level of anxiety correlated positively with the level of physical exhaustion. Patients who coped predominately using social support had the highest scores on the GBB preoperatively, and patients with cognitive coping had the lowest scores on the GBB. A depressive form of coping showed the highest positive correlation with the level of anxiety, preoperatively and postoperatively. The postoperative level of anxiety had a close positive relationship with all the scales of the GBB. Patients who coped through compliant behaviour were likely to deny anxiety. They showed the highest level of somatic complaints postoperatively. Cognitive coping was associated with a decrease in the level of anxiety after the surgery. It is concluded that somatic complaints depend selectively upon the form of coping. Planning psychotherapeutic supportive means should be considered before and after surgery.